Fire frequency and time-since-fire effects on the open-forest and woodland flora of Girraween National Park, south-east Queensland, Australia - Watson, P.; Wardell-Johnson, Grant (Blackwell Publishing Asia, 2004)
The effects of recent fire frequency and time-since-fire on plant community composition and species abundance in open-forest and woodland vegetation in Girraween National Park, south-east Queensland, Australia, were examined. Cover-abundance data were collected for shrub and vine species in at least 10 400-m(2) plots in each of four study areas. Study areas were within one community type and had burnt most recently either 4 or 9 years previously. Variations in fire frequency allowed us to compare areas that had burnt at least three times in the previous 25 years with less frequently burnt areas, and also woodlands that had experienced a 28-year interfire interval with more frequently burnt areas. Although species richness did not differ significantly with either time-since-fire or fire frequency, both these factors affected community composition, fire frequency being the more powerful. Moisture availability also influenced floristics. Of the 67 species found in five or more plots, six were significantly associated with time-since-fire, whereas 11 showed a significant difference between more and less frequently burnt plots in each of the two fire-frequency variables. Most species, however, did not vary in cover-abundance with the fire regime parameters examined. Even those species that showed a marked drop in cover-abundance when exposed to a particular fire regime generally maintained some presence in the community. Five species with the capacity to resprout after fire were considered potentially at risk of local extinction under regimes of frequent fire, whereas two species were relatively uncommon in long-unburnt areas. Variable fire regimes, which include interfire intervals of at least 15 years, could be necessary for the continuity of all species in the community.